Communication Strategy of Adult Pedagogy at the Kamal Agricultural Extension Center - Bangkalan Madura - Rachmad, Teguh Hidayatul; Sasongko, Yohanes Probo Dwi (Nuris Journal of Education and Islamic Studies, 2023)
Education lasts a lifetime. In this case, education is the main capital for the development and progress of every human being. With education conducted by adults, these adults can learn to know and understand what is the need and concern, especially at the Agricultural Extension Center (BPP). In this Institute, adults are fostered and educated within the scope of learning for farmer groups to get to know and learn in an integrated way the procedures for growing rice and caring for it until the harvest which will be carried out later as they get the results. The role of all managers and coaches at the BPP non-formal institution will be a good capital in efforts to develop and foster the world of agriculture in Indonesia, as well as a form of implementation of how adults get appreciation through the education they learn